ENG Repositioning Buginese Women as Shamans: A Gender Communication Perspective in South Sulawesi - Mansah, Abdul Majid (Institut Agama Islam Negeri Kendari, 2025)
This study investigates the evolving role of gender within the Buginese community of South Sulawesi, focusing on shamans, known as sandro, who are integral to healing, spiritual guidance, and community rituals. Historically male-dominated, the role of sandro has been reshaped by recent societal changes that allow women to assume these traditionally male roles. Employing a gender communication framework, the research explores how gendered cultural narratives influence the acceptance, resistance, and adaptation of women as shamans, highlighting the interplay between traditional norms and contemporary gender discourse. This study adopts a feminist perspective, utilizing a phenomenological approach and Standpoint Theory to examine the roles of male and female shamans in decision-making within the community. The findings reveal that women shamans increasingly take on leadership roles, shouldering significant spiritual and social responsibilities, while male shamans often occupy supportive positions. This shift indicates a transformation of traditional gender norms. However, the study also identifies resistance to the role of shamans, often rooted in religious beliefs that challenge the legitimacy of shamanic practices. By examining gender dynamics within the Buginese shamanic tradition, the research enhances our understanding of the relationships between gender, culture, and spirituality. The findings underscore the need to address persistent gender biases to promote greater equality and inclusivity in spiritual practices and community life, emphasizing the importance of a gender-sensitive approach in cultural preservation and social progress.